1986
DOI: 10.1002/chin.198627354
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: New Methods for the Synthesis of Glycosides and Oligosaccharides ‐ Are there Alternatives to the Koenigs‐Knorr‐Method?

Abstract: Dedicated to Professor Rudolf Gompper on the occasion of his 60th birthdayGlycoproteins, glycolipids, and glycophospholipids (glycoconjugates) are components of membranes. The oligosaccharide residue is responsible for intercellular recognition and interaction; it acts as a receptor for proteins, hormones, and viruses and governs immune reactions. These significant activities have stimulated interest in oligosaccharides and glycoconjugates. With their help it should be possible to clarify the molecular basis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
103
0
2

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(105 citation statements)
references
References 1 publication
0
103
0
2
Order By: Relevance
“…The glycosidation sites (5-or 6-OH) of the products was established by NOEsobserved between the anomeric proton (l'-H) and 5-or 6-H, and the coupling constant of Jv%2> value defined the stereochemistry of the anomeric center. 4'-Deoxy monosaccharide derivatives (7,8) were derived from dexylosyl PRMC (C) by successive treatment with NaNO2 and NaBH4 (Method C). Stereochemistry of the 3'eq-OH in compound8 was established by the coupling constants observed in *H NMR(Jr y =9.0, /3 j4'ax= 12.0 Hz).…”
mentioning
confidence: 99%
“…The glycosidation sites (5-or 6-OH) of the products was established by NOEsobserved between the anomeric proton (l'-H) and 5-or 6-H, and the coupling constant of Jv%2> value defined the stereochemistry of the anomeric center. 4'-Deoxy monosaccharide derivatives (7,8) were derived from dexylosyl PRMC (C) by successive treatment with NaNO2 and NaBH4 (Method C). Stereochemistry of the 3'eq-OH in compound8 was established by the coupling constants observed in *H NMR(Jr y =9.0, /3 j4'ax= 12.0 Hz).…”
mentioning
confidence: 99%
“…이런 문제점은 폴리페놀의 당화과정 (glycosylation)을 통하여 합성된 배당체를 이용하여 극복할 수 있다. 배당체의 합성은 화학적 방법으로 가능하지만, 이런 방법은 고온, 고압을 포함하는 조건이 필수적이고 합성된 아 노머(anomer) 물질의 분리 및 환경문제 등을 야기하여 [18] 최 근에는 생물체가 지니는 당 전이 능력을 갖는 효소를 이용한 당 전이 반응(transglycosylation)을 통하여 빠르고 쉽게 생산 하고 있다 [8,13] (Fig. 2).…”
Section: 서 론unclassified
“…SciFinder had just become widely accessible, and using this tool we found that indeed, leaders in the carbohydrate synthesis field had routinely dismissed glycosyl iodides as too reactive to be useful. 1 The search also revealed that there had been some dabbling with glycosyl iodides in the 1970s, but no follow-up studies were reported. 2 Fortunately, the Beilstein database was also available, leading us to a rich carbohydrate literature going back to the early 1900s and the laboratories of Emil Fischer.…”
Section: ■ Introductionmentioning
confidence: 99%